Low–complexity adaptive error–control schemes for real–time scalable video transmission over WLANs. (25th May 2012) - Lee, Chen–Wei; Sung, Tien–Wen; Su, Yih–Ching; Yang, Chu–Sing
In this paper, an adaptive video packet transmission mechanism under WLAN is proposed. In terms of the following characteristics: optimal packet length, layering and scalability of MPEG–4 FGS and Unequal Error Protection (UEP), the low calculation complication is applicable to real–time environments. The findings show that the optimal packet length can be obtained through mathematical analysis according to the current wireless network transmission status and the header overhead. Compared to several distinct scalable video transmission schemes, the simulation results reveal that our transmission scheme is capable of reacting to the varying channel condition with less and smoother quality degradation.